2011
DOI: 10.1016/j.jallcom.2010.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of gelatin mediated silver nanoparticles by laser ablation

Abstract: a b s t r a c tWe successfully prepared colloidal silver nanoparticles (Ag-NPs) using a nanosecond pulsed Nd:YAG laser, = 532 nm, with laser fluence of approximately about 0.6 J/pulse, in an aqueous gelatin solution. The size and optical absorption properties of samples were studied as a function of the laser repetition rates. The results from the UV-vis spectroscopy demonstrated that the mean diameter of Ag-NPs increase with the laser repetition rate increases. The Ag-NPs have mean diameters ranging from appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 23 publications
1
36
0
Order By: Relevance
“…6 Gelatin is a natural biopolymer extracted from the partial hydrolysis of collagen which has good biocompatibility and biodegradability, and has been widely used in wound dressings, drug carriers, and tissue scaffolds in recent years. 7 There are many methods for synthesizing metal nanoparticles, including photo reduction, 8 laser ablation, 9 chemical reduction in aqueous media with different polymer surfactants, 10,11 reduction of chemicals in soft matrices, [12][13][14] reduction of chemicals in solid matrices (eg, mesoporous silicate), 15 and chemical vapor deposition. 16 Silver nanoparticles (Ag-NPs) are widely used as catalysts, [17][18][19] photo-catalysts, [20][21][22] and in surface-enhanced Raman spectroscopy [24][25][26] as well as chemical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…6 Gelatin is a natural biopolymer extracted from the partial hydrolysis of collagen which has good biocompatibility and biodegradability, and has been widely used in wound dressings, drug carriers, and tissue scaffolds in recent years. 7 There are many methods for synthesizing metal nanoparticles, including photo reduction, 8 laser ablation, 9 chemical reduction in aqueous media with different polymer surfactants, 10,11 reduction of chemicals in soft matrices, [12][13][14] reduction of chemicals in solid matrices (eg, mesoporous silicate), 15 and chemical vapor deposition. 16 Silver nanoparticles (Ag-NPs) are widely used as catalysts, [17][18][19] photo-catalysts, [20][21][22] and in surface-enhanced Raman spectroscopy [24][25][26] as well as chemical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] For example, Polyvinylpyrrolidone (PVP) has been used as an effective passivation agent for preparing silver nanoparticles (Ag-NPs) and other metal nanoparticles. 17 One of the green preparation methods of metallic nanoparticles is the polysaccharide method.…”
mentioning
confidence: 99%
“…The experimental apparatus used for laser ablation of metal plate has been described elsewhere. [1][2][3][4] The beam was focused onto the target using a 25 cm focal length lens. The plate was then removed from the glass cell, and the silver nanoparticles were irradiated by another Q-switched Nd:YAG pulsed laser (SL400/SL800 system) of wavelength 532 nm, duration 10 nsec, and pulse energy 60 mJ for 15 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Fabrication of metal nanoparticles by laser ablation of bulk plate in liquid media has been investigated intensively in recent research. [1][2][3][4] The results of these studies have shown that laser beam irradiation onto metal nanoparticles causes fragmentation or fusion of the particles due to photothermal melting. [5][6][7][8][9] Therefore, laser irradiation can be used to control the shape and size of particles.…”
Section: Introductionmentioning
confidence: 99%